Burnout Syndrome and Self-Efficacy Beliefs in Professors - García Padilla, Arlington Antonio (2017)
The presence of the Burnout syndrome in professors may be regarded as a deterioration of their mental health with negative impacts on their job performance. It is known that teachers develop different activities in the areas of teaching, outreach and research. This study aims to analyze the relationship between the Burnout syndrome and self-efficacy beliefs and the academic performance in professors of the psychology and dentistry programs at a private university in the city of Barranquilla. This study is empirical and analytical with a descriptive-correlational designo The study population consisted of 93 teachers of the psychology and dentistry programs. To choose the sample, a non-probabilistic sample was used according to the inclusion and exclusion criteria that allowed selecting a total of 36 teachers who met the criteria for the study. The instruments that were used in this study was the Maslach Burnout Inventory (MBI, 1981) adapted by Seisdedos (1997), and the Teachers' Self-Efficacy Beliefs of Tschannen-Moran and Woolfolk (2001) adapted by Covarrubias and Mendoza (2016). According to the results, it was observed that there is no significant relationship between Burnout, Self-efficacy Belief and the academic performance.